2020
DOI: 10.1590/0101-60830000000239
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors with depression and anxiety in prisoners in South of Brazil

Abstract: Background: Brazil has the third largest prison population in the world. Research in the world has confirmed a high prevalence of mental disorders in this population. Objective: To identify prevalence and associated factors with depression and anxiety in prisoners of the closed prison system. Methods: This is a cross-sectional study with 643 prisoners were interviewed in six prisons in Rio Grande do Sul, Brazil. To evaluate depression and anxiety, the Mini International Neuropsychiatric Interview 5.0 (MINI) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 21 publications
(36 reference statements)
1
11
1
9
Order By: Relevance
“…In the Pelotas 1993 Birth Cohort Study, it was found that robbery was one of the most highly registered violent crimes up to age 18 years ( 20 ), based on official records. Robbery is also one of the three most common crimes that result in imprisonment in Rio Grande do Sul, the province to which Pelotas city belongs ( 32 ). The prevalence of community family victimization and burglary at home over the past 12 months were also high in the current study, a relatively common pattern in low and middle-income countries ( 33 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the Pelotas 1993 Birth Cohort Study, it was found that robbery was one of the most highly registered violent crimes up to age 18 years ( 20 ), based on official records. Robbery is also one of the three most common crimes that result in imprisonment in Rio Grande do Sul, the province to which Pelotas city belongs ( 32 ). The prevalence of community family victimization and burglary at home over the past 12 months were also high in the current study, a relatively common pattern in low and middle-income countries ( 33 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…We conducted the first cross-sectional online survey to identify factors associated with symptoms of depression and anxiety during the first wave of the COVID-19 pandemic in adults living in Qatar. In addition to variables that are typically associated with depression and anxiety including younger age [ 11 ], ethnicity [ 12 ], female [ 13 ], loneliness [ 14 ], and prior history of mental illness [ 15 , 16 ], we investigated several COVID-19 related factors. We predicted that being infected with or having a close friend or relative infected with COVID-19 or having experienced death of a family member or friend or having been quarantined due to COVID-19 would be positively associated with depressive and anxiety symptomology.…”
Section: Introductionmentioning
confidence: 99%
“…This period is after the rst COVID-19 wave had resolved in Qatar and lockdown measures had loosened, but before the second wave had started. In addition to variables that are typically associated with depression and anxiety including younger age (Mo tt et al, 2007), ethnicity (de Wit et al, 2008), female (Naser et al, 2020), loneliness (Vindegaard and Benros, 2020), and prior history of mental illness (Costa et al, 2020;Liu et al, 2020), we hypothesized that the following factors would be associated with a higher risk of depressive and anxiety symptoms: being infected with or having a close friend or relative infected with COVID-19; experiencing death of a family member or friend from COVID-19; being quarantined due to COVID-19; low levels of religiosity, and nding social media COVID-19 related news and updates anxiety provoking.…”
Section: Introductionmentioning
confidence: 99%